2020
DOI: 10.1016/j.jqsrt.2019.106772
|View full text |Cite
|
Sign up to set email alerts
|

Breit and QED contributions in atomic structure calculations of tungsten ions

Abstract: The Fac, Grasp2k, and Mcdfgme codes are compared in three case study of radiative transitions occurring in tungsten ions: (i) Ni1 and Ni2 lines in Ni-like tungsten, (ii) 3p 3/2 −3p 1/2 hyperfine splitting in Cl-like tungsten, and (iii) Kα 1 and Kα 2 lines in W VIII. Various approaches to include Breit interaction term and QED corrections in atomic calculations are examined. Electron correlation effects are also investigated. The presented data may be used to estimate the theoretical uncertainties relevant to i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…The corresponding correction value was perturbatively computed in the RCI calculation through the exchange of a single transverse photon in the low-frequency limit 41,68 . Comparing the Breit contributions obtained from the perturbative approach to calculations in which the Breit term is included in a variational SCF process allows us to estimate the uncertainty due to the perturbative approach 69,70 . Previous studies have found that the magnitude of this effect is less than 0.3% in the Ni-like case (among others) 69,70 and that it is significantly reduced when the active space is expanded.…”
Section: Estimation Of Uncertainties For the Theoretical Valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…The corresponding correction value was perturbatively computed in the RCI calculation through the exchange of a single transverse photon in the low-frequency limit 41,68 . Comparing the Breit contributions obtained from the perturbative approach to calculations in which the Breit term is included in a variational SCF process allows us to estimate the uncertainty due to the perturbative approach 69,70 . Previous studies have found that the magnitude of this effect is less than 0.3% in the Ni-like case (among others) 69,70 and that it is significantly reduced when the active space is expanded.…”
Section: Estimation Of Uncertainties For the Theoretical Valuesmentioning
confidence: 99%
“…Comparing the Breit contributions obtained from the perturbative approach to calculations in which the Breit term is included in a variational SCF process allows us to estimate the uncertainty due to the perturbative approach 69,70 . Previous studies have found that the magnitude of this effect is less than 0.3% in the Ni-like case (among others) 69,70 and that it is significantly reduced when the active space is expanded. Here, we assume the maximum error owing to the perturbative treatment and adopt a 0.5% uncertainty related to the Breit correction.…”
Section: Estimation Of Uncertainties For the Theoretical Valuesmentioning
confidence: 99%
“…Using the GRASP0 code [24], excitation energies and transition probabilities for W 57+ were estimated by Mohan et al [25]. The energy of 3p 3/2 − 3p 1/2 fine splitting in W 57+ was studied by Kozioł [26] using GRASP2K [27], MCDFGME [28,29] and FAC [17] codes.…”
Section: Introductionmentioning
confidence: 99%
“…For autoionizing final states, both the ground configuration 2s 2 2p 6 3s 2 and the lower single-and double-excited configurations 2s 2 2p 6 3lnl' (l = s, p, d and n = 3-5, l' ≤ n−1) of Mg-like Au 67+ ions were included. Using the FAC code (Version 1.1.5) proposed by Gu [17], which included Berit interactions in the zero-energy limit for the exchanged photons, and quantum electrodynamic (QED) effects [31], we carefully calculated the energy levels and radiative and autoionization rates of Al-like Au 66+ ions. Note that configuration mixing between all the radiative final states and the resonant excited states from DR and TR were included in the calculations.…”
Section: Resultsmentioning
confidence: 99%